(untitled) (Bangladesh Journal of Medical Science, 2016)
Bangladesh has achieved remarkable success in improving most of the health indicators over the last couple of decades despite pervasive economic poverty. However, for a sustainable growth health sector should be among the top lists at Governments policy table. Unfortunately, the recent trend in budget allocation portrayed just the opposite and is concerning as expressed by health experts. Over the last seven fiscal years, budgetary allocation for health dropped from 6.2% to 4.3% of total government expenditure. Due to insufficient public spending, out of pocket payment (OPP) is much higher which is about two-third (64.7%) of total health care spending in Bangladesh. Inadequate and inefficient public healthcare and profiteering tendency of the private healthcare sector are two major factors behind such high private spending. Suffering from a massive shortage of health workforce and with such low public funding it would be very difficult for Bangladesh to fight against upcoming challenges like increasing burden of non communicable diseases (NCDs) and emerging threats due to climate change. Bangladesh Journal of Medical Science Vol.15(4) 2016 p.505-510